2022
DOI: 10.1364/ao.447209
|View full text |Cite
|
Sign up to set email alerts
|

Impact of spectral noise shape and correlations of laser beam jitter on acquiring optical links in space

Abstract: We investigate how the probability of acquiring an optical link between a scanning and a target spacecraft depends on the spectral shape, power and dimensionality of the beam jitter, as well as on the choice of detector integration time, beam detection radius and scan speed. For slow scans and long integration times, the probability of failure (Pfail) is determined by the integrated jitter power up to a critical frequency, which we verify by comparing the results of an analytical model to those of Monte Carlo … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 21 publications
3
15
0
Order By: Relevance
“…The analytical model of section 3.3 assumes that a jitter excursion remains quasi constant while the beam passes by SC2, which implies that the beam transit time T pass = 2R d /γ must be much smaller than the width of the jitter auto-correlation function: τ 1/2 2R d /γ. If, on the other hand, the scan speed γ is reduced and the correlation time becomes smaller than T pass , the individual integration windows (in our case ≈ 6) become mutually uncorrelated, which reduces P f ail [16]. Therefore, we expect P f ail to decrease continuously towards lower scan speeds, as also the auto-correlation of the beam jitter evaluated at the transit time r xx (T pass ) decreases with γ.…”
Section: Acquisition Failure Dependency On Scan Ratementioning
confidence: 74%
See 4 more Smart Citations
“…The analytical model of section 3.3 assumes that a jitter excursion remains quasi constant while the beam passes by SC2, which implies that the beam transit time T pass = 2R d /γ must be much smaller than the width of the jitter auto-correlation function: τ 1/2 2R d /γ. If, on the other hand, the scan speed γ is reduced and the correlation time becomes smaller than T pass , the individual integration windows (in our case ≈ 6) become mutually uncorrelated, which reduces P f ail [16]. Therefore, we expect P f ail to decrease continuously towards lower scan speeds, as also the auto-correlation of the beam jitter evaluated at the transit time r xx (T pass ) decreases with γ.…”
Section: Acquisition Failure Dependency On Scan Ratementioning
confidence: 74%
“…However, all these models have in common that the effects of correlations are completely neglected and only RMS values of the amplitudes are used for predicting acquisition probabilities. Therefore, in an extension to our previous analysis, we studied how the spectral distribution and cut-off frequency affect the correlation between integration windows and scanning tracks and found that they strongly impact the acquisition probability [16]. In this paper, we focus on one of the key parameters that may generally be adjusted by the acquisition architect, namely the scan speed, and show it can be tuned to enter 3 different regimes which differ greatly in acquisition probability and duration.…”
Section: Acquisition Modelsmentioning
confidence: 91%
See 3 more Smart Citations